Neuro-PASC is characterized by enhanced CD4+ and diminished CD8+ T cell responses to SARS-CoV-2 Nucleocapsid protein - Visvabharathy, Lavanya; Hanson, Barbara A.; Orban, Zachary S.; Lim, Patrick H.; Palacio, Nicole M.; Jimenez, Millenia; Clark, Jeffrey R.; Graham, Edith L.; Liotta, Eric M.; Tachas, George; Penaloza-MacMaster, Pablo; Koralnik, Igor J. (Frontiers in Immunology, 2023)
Many people with long COVID symptoms suffer from debilitating neurologic post-acute sequelae of SARS-CoV-2 infection (Neuro-PASC). Although symptoms of Neuro-PASC are widely documented, it is still unclear how virus-specific adaptive immunity is affected in these individuals. We report that Neuro-PASC patients exhibit distinct immunological signatures composed of elevated CD4+ T cell responses toward the C-terminal region of SARS-CoV-2 Nucleocapsid protein when examined both functionally and using TCR sequencing. In contrast, Neuro-PASC patients have diminished activation of CD8+ memory T cells and increased IL-6 production to Nucleocapsid. Elevated plasma immunoregulatory and reduced pro-inflammatory and antiviral response signatures were evident in Neuro-PASC patients compared with COVID convalescent controls without lasting symptoms, correlating with worse neurocognitive dysfunction. These data provide new insight into the impact of virus-specific cellular immunity on the pathogenesis of long COVID and pave the way for the rational design of predictive biomarkers and therapeutic interventions.